Databases Selection in a Systematic Review of the Association between Anthropometric Measurements and Dental Caries among Children in Asia - Rokiah Mamikutty; Ameera Syafiqah Aly; Jamaludin Marhazlinda (MDPI AG, 2021)
A comprehensive search for primary studies using a sufficient number and relevant databases is critical to minimise bias and increase the validity of a systematic review. We examined the frequency and choices of databases commonly used to provide an efficient search of primary studies for a systematic review of anthropometric measurements and dental caries among children in Asia. Twelve previous systematic reviews on a similar topic were retrieved from six databases. The frequency and choice of databases used by reviewers were determined from the methods sections. We also identified the lists of other databases usually searched in other reviews. Eligibility criteria for final databases selection were the database's scope, the topic of interest, design of the study, type of article, and the accessibility of the databases. Of the 77 databases identified, previous reviews on this topic used 21 databases, ranging from 2 to 12 databases in each review. Medline, Cochrane Library, Web of Science, and PubMed were employed most frequently. Twenty-six databases were eligible and selected for the present review. Twelve were regional databases to provide comprehensive coverage of primary studies. A systematic approach in selecting appropriate databases for searching primary studies is paramount to reduce errors, ensure coverage, and increase the validity of systematic reviews' conclusions.